Proyecto para introducir mediante un plan de marketing estratégico y operativo las galletas coconut en la ciudad de Guayaquil - Castro Arias, Nelly Jael (2009)
This project produced a degree of market research and analyzed the degree of acceptance and referral of consumers to this new product (Coconut biscuits produced in traditional way, without chemical preparation) in the city of Guayaquil. In the same way, we applied methods of marketing and promotion in both the short and long term, through marketing tools, to effectively fulfill the requirements of the target market and simultaneously maximizing the projected benefits. Also detailed in this work the amount of investment required, both as a fixed deferred, major expenses and costs to cope with the implementation of this project. By examining the economic impact, financial position and estimated the sensitivity analysis, it was determined that the project has a high percentage of return based on cash flows and projected over the next five years